KEMANDIRIAN FINANSIAL: SEBAGAI SARANA DALAM MEMAJUKAN INKLUSI KEUANGAN (Studi Bisnis Pada Masyarakat Kota Tegal) - Bambang Nurdiyansyah; Grace Tianna Solovida (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
The research objectives are to analyze the effect of financial attitudes on financial independence, analyze the effect of financial risk on financial independence, analyze the effect of financial motivation on financial independence, analyze the effect of financial independence on financial inclusion, analyze the effect of financial attitudes on financial inclusion through financial independence, analyze the effects of financial risk. towards financial inclusion through financial independence, analyzing the influence of financial motivation on financial inclusion through financial independence. The study population was all residents of Tegal City as many as 142,105 people and a sample of 100 respondents with the sampling technique, namely purposive sampling method and cluster sampling. Methods of data analysis using SEM with Smart PLS. The results of the study are financial attitude has a positive and significant effect on financial independence, financial risk has no effect on financial independence, financial motivation has no effect on financial independence, financialindependence has a positive effect on financial inclusion, financial attitude has a significant positive effect on financial inclusion through financial independence, risk. finance has no effect on financial inclusion through financial independence, financial motivation has no effect on financial inclusion through financial independence.